Estimations of the Geothermal Energy Potential in The Mount Anak Krakatau Region Based on Derivative Analysis and 3D Model of Gravitational Satellite Data - Gunawan, Belista; Permana, Nanda Ridki (Indonesian Journal of Energy, 2024)
Geothermal energy is a source of renewable energy that has the potential to be produced, considering that Indonesia is in the ring of fire, where there are many volcanoes, one of which is Mount Anak Krakatau. Even though direct exploration is not permitted, at least information on the geothermal system on the mountain can still be obtained using satellite data. Therefore, this study aims to analyze the geothermal energy potential of Mount Anak Krakatau using gravity satellite data with a total of 320 data consisting of gravity disturbance, geoid, and Digital Elevation Model. The data processing describes a 3D model that is correlated with the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) analysis. Based on the results of the residual anomaly map analysis, the low anomaly has a value of -1.85–(-0.89) mGal which is suspected to be associated with magma pockets, and the high anomaly ranges from 0.04–2.13 mGal which is suspected to be associated with the caldera of Mount Anak Krakatau. Based on the results of the FHD and SVD graphical analysis, there are 18 faults that control the geothermal system. Based on the results of 3D modeling trending from west-east it can be seen that there is a clay cap layer with a value density 2.32–2.37 gr/cc at depths of 0–550 m and reservoir layers with density values of 2.23–2.29 gr/cc at depths of 500–1100 m. This geothermal research using the gravity method can be developed and become a reference for future research to calculate the potential for electrification in a research area.